Management Of Diabetes Mellitus Type 2 For Elderly: Taichi Exercise To Reduce Blood Sugar Levels - Zainal Abidin; Ratna Puji Priyanti; Anja Hesnia Kholis; Fahruddin Kurdi (Nursing and Health Sciences Journal (NHSJ), 2021)
Elderly are high risk for the development of type 2 diabetes due to the combined effects of increasing insulin resistance and impaired pancreatic function with aging. Diabetes mellitus is a chronic disease that causes insulin in the pancreas is not effective one of the treatments that can be done by diabetics to reduce blood sugar levels One of them with physical activity, the activity is taichi exercises.The purpose of this study was to investigate the effect of taichi exercises on reducing blood sugar levels in patients with type II diabetes mellitus.The design of this study was pre-experiment one group pre-test and post-test design with a population of 88 patients and a sample of 44 respondents. Research sampling technique used purposive sampling. Data collection with observation sheets. The intervention was carried out four times during 4 weeks. Before the intervention, sugar levels of type II diabetics were classified as moderate as 24 people (54.5%) and high as many as 20 people (45.5%). After the management of taichi exercises sugar levels experienced changes in the categories of good as many as 16 people (36.4%), moderate as many as 20 people (45.5%) and high as many as 8 people (18.2%). Data analized with Wilcoxon Signed Rank test with a significant level α = 0.05, the result ρ-value = 0.001 means ρ-value <α so that there is a significant effect of taichi exercises on decreasing blood sugar levels in patients with type II diabetes mellitus. Blood sugar levels in patients with diabetes mellitus before doing taichi exercises with the number of respondents 44 people mostly experienced changes, evidenced by the level of blood sugar levels from moderate levels to good. Keywords: Elderly, Taichi, Diabetes Mellitus, Blood sugar level